THE INFLUENCE OF BUDGET GOAL CLARITY, INTERNAL CONTROL SYSTEM, REPORTING SYSTEM, WITH ORGANIZATIONAL COMMITMENT AS MODERATING VARIABLE ON THE PERFORMANCE ACCOUNTABILITY OF GOVERNMENT AGENCIES OF LOCAL GOVERNMENT SERDANG BEDAGAI REGENCY - Bayer, Edipson (International Journal of Public Budgeting, Accounting and Finance, 2018)
The purpose of this research was to analyze the effect of budget goal clarity, internal control system, reporting system, with organizational commitment as moderating variable on the performance accountability  of government agencies of local government Serdang Bedagai regency.  This type of research is quantitative that causal research. The population of this research were employees who worked in 47 SKPD’s at Serdang Bedagai regency administration that consisted of subdivision head, and staffs in SKPD so the population were 94 persons. The research methode using cencus methode. The method of data analyse using multiple regression analysis and residual analysis for moderating variable. The result of this study showed that simultaneously variable budget goal clarity, internal control system, reporting system, had significant influence to performance accountability of government agencies on local government Serdang Bedagai regency. Partially, variable internal control system, and reporting system influence positive significant on the quality of  performance accountability  of government agencies at local government Serdang Bedagai regency, but variable budget goal clarity influence not significant on performance accountability  of government agencies of local government Serdang Bedagai regency. The organizational commitment as moderating variable could moderated the relationship between variable budget goal clarity, internal control system, reporting system with the performance accountability  of government agencies of local government Serdang Bedagai regency.